Storage Temperature on the Product Quality of Several Pro Coffee Variants That Contain (Bacillus cereus SN7) - Farisy, Muhammad Fhito Al; Feliatra, Feli; Batubara, Ummi Mardhiah (Journal of Coastal and Ocean Sciences, 2025)
This study aims to analyze the effect of storage temperature on microbial growth in several pro coffee variants and to investigate the impact of storage temperature on the quality of pro coffee containing B. cereus SN7. The coffee variants used were original, latte, original jelly, and latte jelly at temperatures of 10, 25, and 37°C for 7 days of storage. Microbial growth was observed using the total plate count method, while the pro coffee quality was analysed using the organoleptic test. The results showed that low storage temperatures can inhibit microbial growth and maintain the quality of pro coffee. The lowest total number of microbes was found in the original variant with a storage temperature of 10°C, with a value of 0.11 × 103 CFU/mL, and the highest total number of microbes was found in the latte jelly variant with a storage temperature of 25°C, with a value of 3.476 × 103 CFU/mL. In the organoleptic test, the highest value was found in the latte variant coffee at a storage temperature of 10°C, categorized as 'very like', with a value of 35% for taste, 30% for aroma, and 30% for colour. The effect of temperature on the product quality of several probiotic coffee variants containing B. cereus SN7 showed a significant difference (p < 0.05) in microbial growth and the quality value of the probiotic coffee. Statistical analysis showed the effect of temperature on the product quality of several pro coffee variants containing B. cereus SN7.